2020
DOI: 10.1007/s12020-020-02380-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterisation and clinical correlation of papillary thyroid microcarcinoma

Abstract: Purpose Papillary thyroid microcarcinoma (mPTC) is defined as a papillary thyroid cancer sized 10 mm or less. Despite their generally indolent clinical course and good prognosis, a subset of mPTCs shows potentially aggressive behaviour. Methods To search for predictors of clinical outcome of mPTCs, we retrospectively evaluated the genetic tumour profile of 100 patients (23 M/77 F, mean age ± SD 53.8 ± 13.4 years) with histologically confirmed mPTCs through analysis of BRAF, NRAS and TERT promoter mutations as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 46 publications
2
13
1
Order By: Relevance
“…Interestingly, incidence of DM in this cohort was 6% among PTMC patients (3.3% patients developed DM after a median of 3.2 years of initial diagnosis while 2.7% presented with DM at diagnosis). This relatively high incidence rate among Middle Eastern PTMC patients is in contrast to previous reports from other ethnicities, where DM from PTMC was very rare ( 10 , 12 , 45 48 ). We were intrigued by the occurrence of distance metastasis at this relatively high rate.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…Interestingly, incidence of DM in this cohort was 6% among PTMC patients (3.3% patients developed DM after a median of 3.2 years of initial diagnosis while 2.7% presented with DM at diagnosis). This relatively high incidence rate among Middle Eastern PTMC patients is in contrast to previous reports from other ethnicities, where DM from PTMC was very rare ( 10 , 12 , 45 48 ). We were intrigued by the occurrence of distance metastasis at this relatively high rate.…”
Section: Discussioncontrasting
confidence: 96%
“…( 36 ) have reported the prevalence of TERT promoter mutations in 4.7% (19/404) PTMC from Italy, whereas Sama et al. ( 45 ) found the prevalence to be 2% (2/100) in PTMC from the same population. Three other studies from Asian population reported a frequency of 3.2% (16/504) from Korea ( 39 ), 1.2% (1/86) from China ( 37 ) and 0% (0/26) from Japan ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, TERTp mutations were found in 4.7% of the 431 miPTCs analyzed, but no association between TERTp mutations and aggressive features or clinical outcome was found [53]. Consistent with all these data and the excellent prognosis of PMCs, no [57][58][59][60][61] or very low percentage [52,62] of TERTp mutations have been detected in PMCs, indicating no [52,53,58] or a limited role in risk stratification in PMCs [62]. It remains unknown if the coexistence of BRAF and TERTp mutations could be associated with PMCs with a poor clinical outcome [63].…”
Section: Histopathology-extremely Low Malignancy-microptcmentioning
confidence: 76%
“…Third, the ratio of PTC to other thyroid cancers may also affect the sensitivity of BRAF V600E mutation evaluation since BRAF V600E mutation is absent in follicular thyroid carcinomas and occurs at a lower rate in follicular variants of PTC. 53 Although the BRAF V600E test would allow clinicians to optimize management to avoid surgery for benign nodules, thereby decreasing health costs and postsurgical complications, 54 nearly 20% of PTC cases could not be properly distinguished preoperatively by BRAF V600E mutation detection, even when combined with FNA. This is likely related to the complexity of the carcinogenesis of PTC.…”
Section: Discussionmentioning
confidence: 99%